Examining Firm Size as a Moderator of Efficiency and Liquidity Effects on Profitability - Aufa Salsabila Yan Alfarah; Hadinugroho, Bambang (Universitas Muhammadiyah Pontianak, 2026)
This study examines how efficiency and liquidity affect profitability, and the moderating role of firm size, in IDX-listed transportation and logistics firms (2015–2024). Using 266 firm-year panel data and multiple regression analysis in EViews, the study finds that efficiency and liquidity do not directly affect ROA or ROE. However, firm size significantly moderates their relationship with ROA, with larger firms benefiting more. No such moderation is found for ROE, which is more influenced by firm growth and leverage. These findings highlight the importance of firm size in shaping profitability dynamics in Indonesia’s logistics sector.